A comparative meta-analysis of peripheral 8-hydroxy-2′-deoxyguanosine (8-OHdG) or 8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxo-dG) levels across mood episodes in bipolar disorder. (May 2023) - Çeli̇k, Hidayet Ece ARAT; Tuna, Gamze; Ceylan, Deniz; Küçükgöncü, Suat
Abstract: Objective: Oxidative DNA damage has been associated with the pathophysiology of bipolar disorder (BD) as one of the common pathways between increased medical comorbidity and premature aging in BD. Previous evidence shows increased levels of oxidatively induced DNA damage markers, 8-hydroxy-2′-deoxyguanosine (8-OHdG) or its tautomer 8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxo-dG), in patients with BD in comparison to healthy individuals. With the current research, we aim to analyze data on peripheral (blood or urine) 8-OHdG/8-oxo-dG levels across mood states of BD using a meta-analytical approach. Method: A literature search was conducted using the databases PubMed, Scopus, and Web of Science to identify eligible studies (January 1989 to July 2022). Relevant studies were systematically reviewed; a random-effects meta-analysis and a meta-regression analysis were conducted. Results: The current meta-analysis included 12 studies consisting of 808 BD patients (390 in euthymia, 156 in mania, 137 in depression, 16 in mixed episode, 109 not specified) and 563 healthy controls. BD patients that were currently depressed had significantly higher levels of 8-OHdG/8-oxo-dG than healthy controls, while euthymic or manic patients did not differ from healthy controls. A meta-regression analysis showed sex distribution (being female) and older age to be significantly related to increased 8-OHdG/8-oxo-dG levels. Conclusion: Our findings suggest that 8-OHdG/8-oxo-dG may be a state-related marker of depression in BD and may be affected by older age and female gender. Highlights: Patients with bipolar disorder in depression had higher levels of 8-OHdG compared to healthy controls. 8-OHdG levels didn't differ in other mood states in bipolar disorder compared to healthy controls. 8-OHdG can be a state-dependent marker of depression in bipolar disorder.